In the Wrong Place at the Wrong Time: The Impact of Mass Shooting Exposure on Mental Health - Michele Ubaldi; Matteo Picchio (Institute of Labor Economics (IZA), 2024)
We study the effect of mass shooting exposure on individuals' mental health by using the Panel Study of Income Dynamics. Our identification strategy relies on the quasi-randomness of mass shootings in a staggered difference-in-differences design. We compare changes in mental health outcomes of individuals living in affected cities with changes of matched individuals living in non-proximal and not affected cities. We find that mass shootings have a substantial adverse impact on mental health, which persists for up to six years. This impact is not statistically significant for Black individuals, whereas it is slightly more pronounced among women and older cohorts.
Keywords: C23; I18; K14; 330; mass shooting; mental health; difference-in-differences; dynamic effect